Influence of the contract termination on the acquired ownership of acquirer and third party in Serbian law - Dolović-Bojić Katarina (Anali Pravnog Fakulteta u Beogradu, 2018)
It is indisputable that the principle of causal tradition can be applied at the time of acquisition of ownership. Also, in case of delivery/registration based on non-existent/invalid contract, it will be indisputable obligation of the acquirer to return the thing i.e. it will be followed by removal of the entered right in the register. The same will be in the case when the termination of the contract occurred after delivery/registration, but only if the acquirer did not transfer its ownership. However, if the legal ground - the contract has ceased to exist after registration and ownership transferred to a third party, the situation changes significantly. The scene has been entered by a person who has fulfilled the conditions and thus has become the owner. Termination of the contract as the basis for the acquisition of his predecessor, despite the principle of causal tradition, cannot affect the acquired rights of third parties. A widely accepted view of good faith of the third party as a criterion for determining the impact of contract termination to the acquired ownership is considered absolutely unacceptable.